Dominant CST3 variants cause adult onset leukodystrophy without amyloid angiopathy - Bergner, Caroline G.; Breur, Marjolein; Soto-Bernardini, M. Clara; Schäfer, Lisa; Lier, Julia; Le Duc, Diana; Bundalian, Linnaeus; Schubert, Susanna; Brenner, David; Kreuz, Friedmar R.; Schulte, Björn; Waisfisz, Quinten; et al. (Brain, 2024)
Leukodystrophies are rare genetic white matter disorders that have been regarded as mainly occurring in childhood. This perception has been altered in recent years, as a growing number of leukodystrophies have been described as having an onset in adulthood. Still, many adult patients presenting with white matter changes remain without a specific molecular diagnosis. We describe a novel adult onset leukodystrophy in 16 patients from eight families carrying one of four different stop-gain or frameshift dominant variants in the CST3 gene. Clinical and radiological features differ markedly from the previously described Icelandic cerebral amyloid angiopathy found in patients carrying p.Leu68Asn substitution in CST3. The clinical phenotype consists of recurrent episodes of hemiplegic migraine associated with transient unilateral focal deficits and slowly progressing motor symptoms and cognitive decline in mid to older adult ages. In addition, in some cases acute onset clinical deterioration led to a prolonged episode with reduced consciousness and even early death. Radiologically, pathognomonic changes are found at typical predilection sites involving the deep cerebral white matter sparing a periventricular and directly subcortical rim, the middle blade of corpus callosum, posterior limb of the internal capsule, middle cerebellar peduncles, cerebral peduncles and specifically the globus pallidus. Histopathologic characterization in two autopsy cases did not reveal angiopathy, but instead micro- to macrocystic degeneration of the white matter. Astrocytes were activated at early stages and later displayed severe degeneration and loss. In addition, despite the loss of myelin, elevated numbers of partly apoptotic oligodendrocytes were observed. A structural comparison of the variants in CST3 suggests that specific truncations of cystatin C result in an abnormal function, possibly by rendering the protein more prone to aggregation. Future studies are required to confirm the assumed effect on the protein and to determine pathophysiologic downstream events at the cellular level.
CRIS-Team Scopus Importer:2024-10-25
Keywords: adulthood leukodystrophy; astrocytes; cystatin C; genetic white matter disease; L68N